Study of Some Risk Factors in Patients With Untreated Breast Cancer in Erbil City - Azeez, Sarhang H.; Darogha, Suhaila N. (Science Journal of University of Zakho, 2014)
This study was carried out in Rizgary and Hawler Teaching hospital in Erbil city, from the period of August 2010 to June 2011. A total of 115 women patients with breast tumor (55 malignant and 60 benign) and 40 females as a control group with age ranged (18-71) in both patients and control group were participated, they were matched with patients by age group without any history of breast problem or neoplastic disease and not had any other cancer. Data were collected by interview with patients and control group, a questioner form were provided to each patients which include (age, age at menarche, regularity of menstruation, etc.) and clinical file made for each patient who attends to these two hospitals for each patients for the first time, in spite of histopathological diagnosis. Results indicated obvious relation between risk factor and breast cancer (BC), among these factors is the age; the most frequent age for breast cancer was that at age group (38- 47).Percentage of patients starting age menarche after 12 year was higher when compared with patients starting at or before 12 year. The results showed higher percentage of BC in patients who have regularity menses when compared with irregular menstrual cycle. Age of first pregnancy in 20 years and greater which was higher than other group. The results indicated that the percentage of BBD patients which diagnosed premenopausal was higher than postmenopausal. Higher percentage of breast feeding found in BC patients when compared with bottle feeding. Oral contraceptive pills users occupied higher percentage in patients. Patients which not used hormone replacement therapy (HRT) have higher percentage when compared with patients used HRT. About half of the patients recorded positive family history. The numbers of patients diagnosed as stage third and fourth were higher compared with those stage two, unknown and first stage. According to the type of benign breast disease, the unknown cause showed higher percentage when compared with other types.